Assessment of operant learning and memory in mice born through ICSI. Issue 9 (7th August 2020) - Lewon, Matthew; Wang, Yue; Peters, Christina; Peterson, Matthew; Zheng, Huili; Wang, Zhuqing; Hayes, Linda; Yan, Wei
Abstract: STUDY QUESTION: Are there differences in operant learning and memory between mice born through ICSI and naturally conceived control (CTL) mice? SUMMARY ANSWER: ICSI females exhibited deficits in the acquisition reward learning relative to CTL females, and ICSI males exhibited deficiencies in discrimination learning and memory relative to CTL males. WHAT IS KNOWN ALREADY: Some human outcome studies have suggested that ICSI might be associated with an increased risk of certain cognitive disorders, but only one of two behavioral studies with ICSI mouse models have reported differences between ICSI and CTL females. No studies to date have investigated associative learning in ICSI mice. STUDY DESIGN, SIZE, DURATION: Groups of 36 ICSI mice (18 male, 18 female) and 37 CTL mice (19 male, 18 female) aged 3–6 months were compared in a series of operant learning procedures that assessed acquisition of a new behavior, discrimination learning and memory. In total, 16 ICSI mice (9 male, 7 female) and 17 CTL mice (10 male, 7 female) received follow-up discrimination learning and memory assessments at 12 months of age (6 months after the end of initial training) to evaluate retention and reacquisition of learned performances. PARTICIPANTS/MATERIALS, SETTING, METHODS: Mice received daily operant learning sessions in experimental chambers in which all stimulus events and the recording of responses were automated. Food rewards were delivered for responding under different conditions of reinforcement, which varied by procedure. Subjects received a successive series of sessions of nose poke acquisition training, discrimination training and the delayed-non-matching-to-position memory procedure. Mixed repeated measures ANOVAs in which the between-subjects factor was group (ICSI vs CTL) and the within-subjects factor was repeated exposures to learning procedures (i.e. sessions) were used to analyze data. MAIN RESULTS AND THE ROLE OF CHANCE: In comparisons between all mice (i.e. males and females combined), CTL mice exhibited superior performance relative to ICSI in response acquisition ( P = 0.03), discrimination ( P = 0.001) and memory ( P = 0.007). Sex-specific comparisons between the groups yielded evidence of sexual dimorphism. ICSI females exhibited a deficit in acquisition learning relative to CTL females ( P < 0.001), but there was not a significant difference between CTL and ICSI males. In the discrimination and memory tasks, ICSI males exhibited deficits relative to CTL males ( P = 0.002 and P = 0.02, respectively) but the differences between females in these tasks were not significant. There was no difference in discrimination or memory retention/re-acquisition assessments conducted with mice at 12 months of age. ICSI males and females weighed significantly more than CTL counterparts at all points during the experiment. LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: The study was not blinded. All learning assessments utilized food reward; other assessments of operant, Pavlovian and nonassociative learning are needed to fully characterize learning in ICSI mice and speculate regarding the implications for cognitive function in humans conceived via ICSI. WIDER IMPLICATIONS OF THE FINDINGS: Studying learning and memory processes in mouse models have the potential to shed light on ICSI outcomes at the level of cognitive function. Future research should use multiple learning paradigms, assess both males and females, and investigate the effects of variables related to the ICSI procedure. Studying cognitive function in ICSI is an interdisciplinary endeavor and requires co-ordination between researchers at the genetic and psychological levels of analysis. STUDY FUNDING/COMPETING INTEREST(S): This work was supported, in part, by grants from the NIH (P30GM110767, HD071736 and HD085506 to W.Y.), the Templeton Foundation (61174 to W.Y.) and a New Scholarly Endeavor Grant from the University of Nevada, Reno Office of Research and Innovation (to M.L., Y.W., H.Z., L.H. and W.Y.). The authors declare no competing interests.